Discovery of Melanogenic Bacteria from Anak Krakatau Volcano Soil through Enzymatic, Antioxidant-Based Screening and Its Volatile Metabolic Profiles - Muhammad Asril; Achmad Gus Fahmi; Annisa Maulidia Rahayyu; Taufik Priya Azzahwa; Dian Anggria Sari; Didik Supriyadi (Journal of Multidisciplinary Applied Natural Science, 2026)
Microbial melanin has attracted increasing attention due to its multifunctional properties, particularly its antioxidant activity, making it attractive for biotechnological applications. Volcanic soils represent extreme, metal-rich ecosystems that may harbor melanogenic bacteria with unique metabolic adaptations. This study aimed to isolate and characterize melanin-producing bacteria from the volcanic soil of Mount Anak Krakatau, evaluating their melanogenic capacity, antioxidant activity, and volatile metabolite profiles. Eight bacterial isolates were obtained using tyrosine agar supplemented with CuSO₄ to selectively promote tyrosinase-mediated melanogenesis. Three isolates (AK3, AK5, and AK7) exhibited clear melanogenic phenotypes, as indicated by the progressive development of brown to black pigmentation during cultivation. Tyrosinase activity and L-DOPA concentration showed dynamic changes throughout the production period, with isolate AK5 demonstrating the highest tyrosinase activity (4,500 ± 135.27 U/mL) and L-DOPA accumulation (up to 89.82 ± 0.13 µg/mL), reflecting efficient biotransformation of L-tyrosine. The antioxidant activity of free-cell supernatants, evaluated using the ferric reducing antioxidant power (FRAP) and total antioxidant capacity (TAC) assays, yielded substantial values, with AK5 exhibiting the highest performance among the testing isolates and further identified as Bacillus cereus AK5 by phylogenetic analysis of 16S rRNA gene sequences. Gas chromatography–mass spectrometry (GC–MS) analysis revealed distinct, isolate-specific volatile organic compound (VOC) profiles, which we hypothesize may reflect adaptive secondary metabolic responses to oxidative stress generated during melanogenesis, though this link requires further experimental validation. To the best of our knowledge and based on the available literature, this study reports the first isolation of melanin-producing bacteria with antioxidant potential from volcanic soil at Mount Anak Krakatau, highlighting this environment as a promising source of melanogenic bacteria for pharmaceutical applications.